Monument marks grave of famous horse! (Cimarron, New Mexico Cimarron Legend, 1992)
Article on the monument that marks the death of a famous rodeo horse, Yellow Gold.
Master List item # 2
File location is in the Raton File Cabinet
Keywords: George, Gibb; Local History; Rodeo; Horse; Death; Owner; Monument; Raton, New Mexico; Trinidad, Colorado